Replacing Local Labors Instead of Expatriate in Jordan Tourism Sector - Ehab Abdul Raheem Alshatnawi (European Scientific Journal, ESJ, 2016)
The objective of this current study is to identify the issue of tourist expatriate labor, its effects on the touristic and economic levels, its ways of evaluation, the manner of dealing with its reasons and motivations, and the ways of replacing it with local labor. However, this labor is able to fill the gap to and from a pure Jordanian touristic product. In addition, it is able to obtain the maximum benefit from tourist activity. The results of the study revealed that the expatriate labor represents 17.6% of the total labor in the Jordanian tourist sector. Therefore, most of these labors are concentrated in hotels and tourist restaurants. Tourism is one of the Jordanian sectors that do not attract local labor, but are attractive to expatriate labor. The expatriate labor in the Jordanian tourist sector is complementary. Hence, it is not a substitute for the tourist professions. The study recommended the need to develop local tourist workers by holding courses for the Jordanian workers in the tourist hotels and restaurants. Also, training on lingual and specialized tasks which focuses on the medium university education should be provided for them. Also, vocational training corporations should be organized. This in turn fills the gap of the tourist activities that attract expatriate labor and amendment legislation and laws relating to wages and the nature of work in the tourism sector. Hence, this is aimed to attract local tourist labor.